Update on pediatric gastroparesis: A review of the published literature and recommendations for future research. Issue 3 (18th December 2019) - Kovacic, Katja; Elfar, Walaa; Rosen, John M.; Yacob, Desale; Raynor, Jennifer; Mostamand, Shikib; Punati, Jaya; Fortunato, John E.; Saps, Miguel
Abstract: Background: Due to scarcity of scientific literature on pediatric gastroparesis, there is a need to summarize current evidence and identify areas requiring further research. The aim of this study was to provide an evidence‐based review of the available literature on the prevalence, pathogenesis, clinical presentation, diagnosis, treatment, and outcomes of pediatric gastroparesis. Methods: A search of the literature was performed using the Preferred Reporting Items for Systematic Reviews and Meta‐analyses guidelines with the following databases: PubMed, EMBASE, Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, Cochrane Central Register of Controlled Trials, and Web of Science. Two independent reviewers screened abstracts for eligibility. Key Results: Our search yielded 1085 original publications, 135 of which met inclusion criteria. Most articles were of retrospective study design. Only 12 randomized controlled trials were identified, all of which were in infants. The prevalence of pediatric gastroparesis is unknown. Gastroparesis may be suspected based on clinical symptoms although these are often non‐specific. The 4‐hour nuclear scintigraphy scan remains gold standard for diagnosis despite lack of pediatric normative comparison data. Therapeutic approaches include dietary modifications, prokinetic drugs, and postpyloric enteral tube feeds. For refractory cases, intrapyloric botulinum toxin and surgical interventions such as gastric electrical stimulation may be warranted. Most interventions still lack rigorous supportive data. Conclusions: Diagnosis and treatment of pediatric gastroparesis are challenging due to paucity of published evidence. Larger and more rigorous clinical trials are necessary to improve outcomes. Abstract : Overview of suggested, step‐wise approach to pediatric gastroparesis.